Using social media and subjective well-being during COVID-19 pandemic - Yahiiaiev, Illia; Novoselska, Alina; Keller, Vladyslava; Savych, Marta (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The relevance of the topic is related to the psychosocial consequences of the COVID-19 pandemic. The aim is to study the subjective well-being during the beginning of the pandemic and introduction of the quarantine measures and their connection to social media activity. The methods employed in the present study include various types of questionnaires, namely the Positive and Negative Affect Schedule (PANAS) (Watson, Clark & Tellegen, 1988), the Satisfaction With Life Scale (SWLS) (Diener, Emmnos, Larsen, & Griffin, 1985), the General Self-Efficacy Scale (Schwarzer & Jerusalem, 1995), and an original questionnaire developed to study the impact of the pandemic and the respondents’ understanding and perceptions of it. The findings of the quantitative analysis show that the subjective well-being during the pandemic is connected to the use of social media, life satisfaction, health risks assessments and economic consequences, leisure time and the level of self-efficacy. A qualitative analysis indicates that at the beginning of the COVID-19 pandemic in Ukraine the negative predictions of the consequences of both the pandemic and the implemented quarantine measures prevail among the subjects. A longitudinal study during one month has found a reduction in health concerns, and respondents began to assess the threat to their health and economic consequences of the coronavirus pandemic as less serious than at the beginning. Thus, it can be concluded that from a short-term perspective the negative affect, especially the levels of fear and anxiety, decreased, whereas the level of the positive affect did not change.
Keywords: psychological well-being; subjective well-being; pandemic; life satisfaction; social media; conspiracy theories; COVID-19